2013
DOI: 10.1111/jspn.12026
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric nurses' postoperative pain management practices: An observational study

Abstract: The use of pain scores to guide treatment choices needs further debate. Future research should explore the implications of divorcing treatment from pain scores on children's pain experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
41
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 66 publications
3
41
0
Order By: Relevance
“…Furthermore, the Twycross (2007) study observed 13 nurses to determine whether postoperative pain in children was accurately managed based on the current best practice guidelines. Although this was a qualitative assessment based on field notes, the authors determined that the nurses appeared to be inconsistent in their evaluations of pain following drug administration (Twycross 2007). These findings are consistent with the current study and Stomberg et al's (2003) study.…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, the Twycross (2007) study observed 13 nurses to determine whether postoperative pain in children was accurately managed based on the current best practice guidelines. Although this was a qualitative assessment based on field notes, the authors determined that the nurses appeared to be inconsistent in their evaluations of pain following drug administration (Twycross 2007). These findings are consistent with the current study and Stomberg et al's (2003) study.…”
Section: Discussionsupporting
confidence: 87%
“…Specifically, the pain experienced by pediatric patients is routinely undertreated as children are not usually effectively medicated, and the pain levels that pediatric patients experience during hospitalization is often not adequately assessed and managed by nurses and hospital management (Kortesluoma, Nikkonen, & Serlo, 2008;Mathews, 2011;Twycross & Collins, 2013). Pediatric pain-management practices continue to fall short of the ideal (Shrestha-Ranjit & Manias, 2010;Twycross, Finley, & Latimer, 2013), with hospitalized children experiencing moderate to severe unrelieved pain postoperatively (Fortier, Chou, Maurer, & Kain, 2011;Shrestha-Ranjit & Manias, 2010;Taylor, Boyer, & Campbell, 2008). Pediatric patients with having postoperative pain are usually to experience difficulty coughing, deep breathing and mobilitation, thereby uncontrolled postoperative pain in children may increase postoperative complications, hospital stays and costs (Payakkaraung et al, 2010;Taddio et al, 2009;Twycross, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The assessment and management of pain in children is the subject of ongoing debate. Hospitalized children routinely endure unresolved pain during procedures required for the diagnosis and treatment of their illnesses (Buscemi, Vandermeer, & Curtis, ; Stevens et al., ; Taylor, Boyer, & Campbell, ; Twycross, Finley, & Latimer, ). International associations have mandated children's right to optimal alleviation of their pain (Finley, Franck, Grunau, & von Baeyer, ; International Association for the Study of Pain, ; World Health Organization and International Association for the Study of Pain, ).…”
mentioning
confidence: 99%
“…Nursing factors identified as preventing the integration/uptake of current evidence to lead pain practices are being examined (Cummings, Hutchinson, Scott, Norton, & Estabrooks, ; Scott‐Findlay & Estabrooks, ; Twycross et al., ). Procedure‐related pain in particular has been cited throughout the pediatric pain literature as significantly impacting children's hospital experiences.…”
mentioning
confidence: 99%
See 1 more Smart Citation